Optical solitons for the Schrodinger-Hirota equation with power law nonlinearity by the Backlund transformation - Kilic, Bulent; İnç, Mustafa (Elsevier Gmbh, 2017)
This paper presents dispersive optical solitons that are governed by the Schrodinger-Hirota equation (SHe) with power law nonlinearity. Optical solitons and solitary wave solutions are sought for the SHe with power law nonlinearity in the sense of the Backlund transformation. Some general and specific solitons of the SHe are obtained in this work. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Backlund transformation; SHe; With power law nonlinearity; Soliton